Buka Luwur Sunan Kudus sebagai Praktik Keagamaan Islam Nusantara: Ritual, Sakralitas Simbolik, dan Kontestasi Makna “Berkah” (Studi Persepsi Warga Nahdlatul Ulama di Kudus) - Rika Fitri Devina Varadila (Lakpesdam PCNU Kota Salatiga, 2024)
The Buka Luwur tradition at the Tomb of Sunan Kudus represents an Islamic Nusantara religious practice that illustrates the encounter between Islamic values and local cultural expressions through ritual sequences and symbols embedded in Kudus society. This study addresses two research questions: (1) how Buka Luwur is constructed as an Islamic Nusantara religious practice through the simultaneous workings of ritual mechanisms, sacrality, and symbols (luwur cloth, nasi jangkrik, heirlooms/keris, and jamasan water) within the santri/NU community in Kauman; and (2) how differences in perception between Kauman residents as communicators/tradition managers and outside participants as communicants shape the phenomenon of ngalap barokah and create potential miscommunication. Employing a qualitative approach with a descriptive–analytical case study design, the study draws on field data (in-depth interviews with key informants) and supporting sources (documents and relevant literature), analyzed through frameworks of ritual–sacrality–symbol and perception and socio-religious communication. The findings show that Buka Luwur functions as a socio-religious institution that regulates sacred time (the peak on 10 Muharram), affirms sacred space (the Menara Mosque complex and the Tomb of Sunan Kudus), and structures collective roles, while ritual objects undergo sacralization through karomah narratives and collective memory. At the same time, divergent perceptions emerge: Kauman residents tend to interpret the ritual primarily as veneration and almsgiving, whereas some outside participants emphasize practical blessings mediated through objects, which in turn fosters ngalap barokah practices and may generate miscommunication. This study recommends strengthening meaning-making communication by tradition managers through tauhid-oriented educational narratives, proportionate explanations of symbols, and improved governance of processions and the distribution of blessings to ensure order, thereby keeping the ritual’s core functions almsgiving, veneration, and social cohesion dominant.